2022
DOI: 10.1002/adma.202110356
|View full text |Cite
|
Sign up to set email alerts
|

Steric Engineering Enables Efficient and Photostable Wide‐Bandgap Perovskites for All‐Perovskite Tandem Solar Cells

Abstract: Wide‐bandgap (WBG, ≈1.8 eV) perovskite is a crucial component to pair with narrow‐bandgap perovskite in low‐cost monolithic all‐perovskite tandem solar cells. However, the stability and efficiency of WBG perovskite solar cells (PSCs) are constrained by the light‐induced halide segregation and by the large photovoltage deficit. Here, a steric engineering to obtain high‐quality and photostable WBG perovskites (≈1.8 eV) suitable for all‐perovskite tandems is reported. By alloying dimethylammonium and chloride int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 52 publications
1
68
0
Order By: Relevance
“…The perovskite film seemed to be intact and dense, indicating that no degradation occurred during the storage period. After aging, the SEM image of the TPO-encapsulated cell showed no obvious change despite the increased grain boundary quantity, which might be a result of light-induced degradation [14,31]. For EVA and POE groups, abundant pinholes appeared in perovskite bulk, and the gap between the perovskite layer and charge transport layer tended to be sharpened, inferring that both the perovskite film and interface encountered attenuation.…”
Section: Resultsmentioning
confidence: 98%
“…The perovskite film seemed to be intact and dense, indicating that no degradation occurred during the storage period. After aging, the SEM image of the TPO-encapsulated cell showed no obvious change despite the increased grain boundary quantity, which might be a result of light-induced degradation [14,31]. For EVA and POE groups, abundant pinholes appeared in perovskite bulk, and the gap between the perovskite layer and charge transport layer tended to be sharpened, inferring that both the perovskite film and interface encountered attenuation.…”
Section: Resultsmentioning
confidence: 98%
“…22 Moreover, our recent study showed that alloying both at the A-site and X-site can modulate the crystal structure and electron orbital configuration synchronously, which allowed for obtaining ∼1.8 eV WBG perovskites with only 25% Br. 23 Through systematic compositional engineering, we found that adding both DMAI and MAPbCl 3 (10 mol % of DMAI and 5 mol % of MAPbCl 3 ) into the Cs 0.4 FA 0.6 Pb(I 0.75 Br 0.25 ) 3 perovskite enabled the optimal bandgap for tandem and minimized the lattice strain and trap densities simultaneously (Figure 2b). Thus, the improved WBG perovskite, with a high PCE of 17.7% and a V oc of 1.26 V, exhibited considerably suppressed light-induced phase segregation and maintained 90% of their initial performance after 1 000 h maximum power point (MPP) tracking under 1 sun illumination.…”
Section: Optimization Of Perovskite Absorbersmentioning
confidence: 99%
“…(b) Lattice strain analysis and charge carrier dynamics of WBG perovskite films. Reproduced with permission from ref . Copyright 2022 Wiley.…”
Section: Optimization Of Perovskite Absorbersmentioning
confidence: 99%
“…Our group advanced that the light-induced halide segregation was not only caused by the content of Br, but also closely related to lattice strain. By alloying DMA and Cl into the mixed-cation mixedhalide perovskites, targeted bandgaps (1.8 eV) are obtained with only 25 mol% Br while the lattice strain and trap densities are simultaneously minimized [26] (Fig. 3c, d).…”
Section: Wide-bandgap Subcellmentioning
confidence: 99%